CASE STUDY OF PERTAMINA SUBHOLDING ESTABLISHMENT: RESTRUCTURING MULTI-BUSINESS COMPANY TO SUPPORT CORPORATE STRATEGY - Alicia Irzanova (Sean Institute, 2023)
The case study in June is related to the establishment of oil and gas subholding carried out by Pertamina in 2021. Pertamina has a vision to become a worldclass energy company and aspirations to reach a market value of 100 billion USD. The oil and gas business is very competitive. As the business grows and shareholders' aspirations to increase Pertamina's size, Pertamina's business becomes more complex. Pertamina restructured its business to be simpler by forming subholdings. This journal will analyze Pertamina's subholding formation strategy, including what challenges Pertamina faces, how the formation of subholding can be a solution to these challenges and how Pertamina ensures that the subholding formation strategy can have a positive impact on it. This research is quantitative and explanatory. To answer this question, researchers interviewed officials at Pertamina, made observations and studied Pertamina documents such as RJPP, RKAP, Annual Report and others. The results of the interview and observations were then analyzed for suitability. From the analysis results, it can be concluded that Pertamina took steps to change its structure from functional to multidivisional to support its strategy and face the challenges of its business complications. This structure supports Pertamina's business because it provides an opportunity to optimize synergies between subsidiaries to provide maximum value. Pertamina formulates its corporate parenting methods in various forms of direction and supervision to ensure that the strategy has a positive impact. This restructuring trend occurs in various businesses both in Indonesia and abroad. In 2023, multinational technology company Alibaba will also restructure. Domestically, the Ministry of SOEs is currently actively restructuring SOEs. Pertamina's process and strategic choices in this study can be a reference for companies that will carry out restructuring.